NH2-functionalized carbon-coated Fe3O4 core–shell nanoparticles for in situ preparation of robust polyimide composite films with high dielectric constant, low dielectric loss, and high breakdown strength. Issue 109 (10th November 2016) - Fang, Xinliang; Wang, Shanfeng; Li, Yanxiao; Liu, Xiaoyun; Li, Xinxin; Lin, Shaoliang; Cui, Zhong-Kai; Zhuang, Qixin
Abstract : Thermostable amine-functionalized carbon-coated Fe3 O4 /polyimide composites with high dielectric constant and low dielectric loss were created at a low percolation threshold. Abstract : Novel Fe3 O4 /polyimide (PI) composite films with extraordinary dielectric properties were prepared via in situ polymerization of PI in the presence of 4, 4′-diaminodiphenyl ether (ODA), pyromellitic dianhydride (PMDA) and compatible amine-functionalized carbon-coated Fe3 O4 nanoparticles (Fe3 O4 @C–NH2 ). Fe3 O4 nanoparticles prepared via solvothermal reaction were coated with crosslinked glucose and then surface-grafted via carbodiimide coupling. The core–shell structure of Fe3 O4 @C–NH2 was thereafter obtained with amine functionalities on the carbonized-glucose shell. Homogeneous dispersion of Fe3 O4 @C–NH2 and strong interfacial covalent bonding on the shell surface contributed to high dielectric constants ( ε ) and extremely low dielectric losses (tan  δ ) in the composite films. The highest dielectric constant of the composite films was 58.6 at 1 kHz when the Fe3 O4 @C–NH2 composition was 1.13 vol%, as well as a low dielectric loss of 0.0091 and a high breakdown strength of 126.5 ± 11.3 MV m −1 were observed without considerable sacrifice of the thermal stability and mechanical properties.